2023
DOI: 10.1088/1361-648x/acee3d
|View full text |Cite
|
Sign up to set email alerts
|

Defining optimal thickness for maximal self-field Jc in YBCO/CeO2 multilayers grown on buffered metal

A Tuomola,
E Rivasto,
M M Aye
et al.

Abstract: The effect of multilayering YBa2Cu3O6+x (YBCO) thin films with sequentially deposited CeO2 layers between YBCO layers grown on buffered metallic template is investigated to optimize the self-field critical current density J c(0). We have obtained that the improvement in J c(0) clearly depends on the YBCO layer thickness and temperature, where at high temperature J c(0) can be increased even 50 % when compared with the single layer YBCO films. Based on our experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…In contrast, for example, when using a CeO 2 interlayer, a strained region of several nanometers thick consistently forms above the CeO 2 interlayer. 56 Finally, based on the literature, the partial substitution of Ca 2+ ions at Y 3+ sites in YBCO alters the carrier concentration and affects the transfer of charges from the CuO chains to the conducting CuO 2 planes. 57,58 The fixed charge is entirely offset by oxygen defects, resulting in a slightly reduced equilibrium oxygen content, which also contributes to a lower superconducting transition temperature.…”
Section: ■ Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, for example, when using a CeO 2 interlayer, a strained region of several nanometers thick consistently forms above the CeO 2 interlayer. 56 Finally, based on the literature, the partial substitution of Ca 2+ ions at Y 3+ sites in YBCO alters the carrier concentration and affects the transfer of charges from the CuO chains to the conducting CuO 2 planes. 57,58 The fixed charge is entirely offset by oxygen defects, resulting in a slightly reduced equilibrium oxygen content, which also contributes to a lower superconducting transition temperature.…”
Section: ■ Resultsmentioning
confidence: 99%
“…These techniques have been shown to enhance the crystalline quality of each sublayer, reducing the likelihood of defect formation in subsequent deposition intervals. 55,56 Second, the underlying Ca-doped YBCO layer serves as an ideal foundation for the 4% BZO-doped YBCO layer. Notably, Ca-doped YBCO exhibits average in-plane and out-of-plane lattice parameters (a = 3.83 Å, b = 3.88 Å, and c = 11.71 Å) that closely match those of BZO-doped YBCO.…”
Section: ■ Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, it can be greatly affected by the deposition process. As an example, we have previously shown that the PLD process can be modified to produce APC-free YBCO films with significantly higher crystalline quality [31,32]. While the condition J c,v (f = 0) = 0 persists to hold for an ideal YBCO film at all temperatures, its validity even for the highest quality experimentally produced YBCO films can be questioned at high temperature range.…”
Section: Effect Of Temperaturementioning
confidence: 99%